Calcium consumption by nursing mothers and children from risk groups on decreased mineral bone density in different age periods under conditions of the city of Tomsk - Ye. I. Kondratiyeva; Ye. G. Gaprindashvili; N. A. Barabash; S. S. Stankevich; N. A. Ryzhakova; G. N. Yankina; T. A. Shemyakina (Бюллетень сибирской медицины, 2009)
We have studied the calcium consumption by nursing mothers and children from risk groups on decreased mineral bone density in different age periods under conditions of Tomsk. The calcium content in breast milk in the first six month of lactation was determined by the method of instrumental neutron-activation analysis. It has been found that the calcium consumption by the most nursing mothers corresponded to physiological norms. In the lactation dynamics, the calcium content in the breast milk decreased at the third month and increased at the sixth month of lactation. The average calcium consumption was (834,3 ± 132,3) mg in children aged of 1—3 and (959,0 ± 99,5) mg/day in children of 4—6 years old. Among schoolchildren, the average calcium consumption was (860,3 ± 98,2) mg/day in the age of 7—10 and (777,9 ± 59,3) mg/day in eth age of 11—18. It is 1,2—1,6 times lower than the recommended norm. In teenagers, the calcium deficit in food is more often compared to preschool children.